2018
DOI: 10.1038/s41420-018-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

The p53 activator overcomes resistance to ALK inhibitors by regulating p53-target selectivity in ALK-driven neuroblastomas

Abstract: Anaplastic lymphoma kinase (ALK) is an oncogenic receptor tyrosine kinase that is activated by gene amplification and mutation in neuroblastomas. ALK inhibitors can delay the progression of ALK-driven cancers, but are of limited use owing to ALK inhibitor resistance. Here, we show that resistance to ALK inhibitor in ALK-driven neuroblastomas can be attenuated by combination treatment with a p53 activator. Either ALK inhibition or p53 activator treatment induced cell cycle arrest, whereas combination treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…Thus, ALK may be involved in M phase progression. In addition, mitotic index was reduced by ALK knockdown ( Figure 2B), which is in agreement with a previous study describing the prolongation of cell cycle progression in G1 phase [25]. Furthermore, stable cells that express HA-tagged wild-type ALK (ALK-HA) upon Dox treatment were established from SH-SY5Y cells (SH-SY5Y/ALK-HA) ( Figure S4).…”
Section: Knockdown Of Alk Causes M Phase Delaysupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, ALK may be involved in M phase progression. In addition, mitotic index was reduced by ALK knockdown ( Figure 2B), which is in agreement with a previous study describing the prolongation of cell cycle progression in G1 phase [25]. Furthermore, stable cells that express HA-tagged wild-type ALK (ALK-HA) upon Dox treatment were established from SH-SY5Y cells (SH-SY5Y/ALK-HA) ( Figure S4).…”
Section: Knockdown Of Alk Causes M Phase Delaysupporting
confidence: 91%
“…Inhibitor treatment during release from RO-3306 treatment did not reduce the mitotic index, thereby eliminating direct suppression of mitotic entry and acceleration of mitotic exit as an explanation. It has been reported that ALK inhibitors induce cell cycle arrest in the G1 phase by reducing the gene expression levels of cell cycle-related proteins (Cyclin D1, D3, and E2F1) and increasing gene expression levels of p27 [25]. Therefore, if ALK knockdown prolongs cell cycle length, it results in relatively lower mitotic index.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that our SNU‐based method would have little effect on cellular behaviors, because products of dsDNA could not be transcripted into mRNA for the subsequent translations into functional proteins. This is due to the absence of binding sites for DNA polymerase as well as the lack of enhanced promoters, activators or RNA interferences for realization of dsDNA's function . Furthermore, the reaction time of present method is much shorter than reports that demonstrated the amplification has no obvious effect on cellular behaviors .…”
Section: Resultsmentioning
confidence: 91%
“…The inhibition of p63 function mediated by the interaction with mutant p53 (both the R175H and R273H mutants) represses SHARP-1 (Basic Helix-Loop-Helix Family Member E41) and Cyclin G2 expression, promoting cell migration and invasion. Phospho-SMAD2 (SMAD family member 2), a component of the transforming growth factor beta (TGFβ) signaling pathway that serves as a scaffold for p53-p63 complex assembly, plays a key role in this process ( Figure 2A) [88,89]. In addition, the mutant p53-dependent suppression of p63 activity increases the Rab coupling protein (RCP)-driven recycling of α5β1 integrin and EGFR (epidermal growth factor receptor) to the cell surface, leading to the activation of Rho and PKB/Akt signaling that promote cell migration and invasion [90].…”
Section: Effect Of Mutant P53 Gof On P53 Family Members: Tumor Invasimentioning
confidence: 99%